Social functioning of elderly persons with malignant diseases - Berat, Svetlana; Nešković-Konstantinović, Zora; Nedović, Goran; Rapaić, Dragan; Marinković, Dragan (Vojnosanitetski pregled, 2014)
Background/Aim. Malignant disease, its treatment and consequences of treatment can often lead to social marginalization and reduced quality of life. The aim of this research was to determine how elderly patients with malignant diseases function in their social environment. Methods. Sociodemographic questionnaire and interview were used to investigate a group of 49 elderly persons undergoing adjuvant chemotherapy treatment against early carcinomas (P1), and a group of 51 elderly persons with advanced stages of cancer undergoing systemic chemotherapy (P2). There were two cycles of assessment: one just before the beginning of the first cycle of adjuvant or systemic chemotherapy, and the other three months later. The research paradigm was based on the relation between individual treatment and the impact of the malignant disease on functional and social incompetence. The obtained findings were compared with the group of 50 healthy elderly people (K) who share the same relevant features but do not suffer from malignant diseases. Results. It was found that most healthy older people live in share house, whereas those who suffer from malignant diseases mostly live in separate households. In both groups of patients and healthy group older people are mostly taken care of by their children. Individuals in both groups of patients have been frequently visited by their relatives during initial stages of treatment, unlike the elderly people in the control group. However, the difference did not reach a statistical significance. Three months after the beginning of chemotherapy, there was a statistically relevant difference in favor of the group undergoing adjuvant treatment. Home visits eventually become less frequent, whereas communication by telephone becomes more frequent. It was also found that visits by friends and neighbors are statistically more frequent among subjects who undergo adjuvant treatment, both before the treatment began and three months later when compared to other groups. Conclusion. Our research shows that elderly people are subject to social exclusion, especially those with malignant diseases. Special care should be dedicated to monitoring of social functioning during treatment of patients with malignant disease considering the detected trend of deterioration and significance for further recover and cure.